THE TELATIONSHIP OF ANXIETY, COMPLIANCE, AND KNOWLEDGE ON THE QUALITY OF LIFE OF HEMODIALISIS PATIENTS AT THE HEMODIALISIS INSTALLATION OF THE HOSPITAL CILEUNGSI - Yurizal, Yurizal; Suara, Mahyar (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Quality of life is an individual's perception of happiness in life, influenced by personal values, culture, and the environment. Chronic Kidney Disease (CKD) is a permanent kidney disorder that affected approximately 0.38% of the Indonesian population in 2018, with a high prevalence rate in West Java Province (over 52,000 cases). Understanding the risk factors for CKD in West Java is crucial for better prevention and management, as well as recognizing the impact of anxiety and compliance on the quality of life. Purpose: To investigate the influence of anxiety, compliance, and knowledge on the quality of life of patients in the hemodialysis unit of RSUD Cileungsi. Methods: This analytical cross-sectional study included a total sample of 40 hemodialysis patients at RSUD Cileungsi. Results: Among the participants, 32.5% experienced moderate anxiety, 27.5% had mild anxiety, 30.0% had no anxiety, and 10.0% had severe anxiety. The majority of patients, specifically 35.0%, demonstrated a very high level of compliance, 30.0% had a high level of compliance, 27.5% had a moderate level of compliance, and 7.5% had low compliance. Regarding knowledge, 34.0% of patients had excellent knowledge, 22.5% had good knowledge, 32.5% had fair knowledge, and 10.0% had poor knowledge. There was a significant influence observed between anxiety, compliance, and knowledge on the quality of life of patients in the hemodialysis unit of RSUD Cileungsi (p-value 0.000). Conclusion: This study identified a significant influence of anxiety, compliance, and knowledge on the quality of life of patients in the hemodialysis unit of RSUD Cileungsi. It is hoped that these findings will enhance healthcare professionals' awareness of the importance of addressing these factors in hemodialysis patients.